Ta’tsīr Wasīlah al-Ghāz al-Faqratiyyah Lī Tarqiyah Natā’ij at-Ta‘allum Mahārah al-Qirā’ah ‘Inda Thalabah al-‘Aliyah - Nisa, Kurnia Lailatun; Syaifullah, Muhammad; Amalia, Dian Risky (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Reading skill is one of the important competencies in learning Arabic. However, many students still experience difficulties in understanding reading texts and organizing ideas coherently, so appropriate learning media are needed to support the learning process. This study aims to determine the effect of the use of paragraph puzzle media on improving the learning outcomes of reading skills of grade X students at Islamic Senior High School Ma'arif Raudhatut Thalibin Metro, Lampung. This study uses a quantitative approach with a quasi-experimental method and Nonequivalent Control Group Design. The research sample totaled 29 students divided into experimental classes and control classes. Data collection is carried out through tests and non-tests, namely pretest and posttest, observation, interviews, and documentation. Data were analyzed using the Shapiro–Wilk normality test, the Levene homogeneity test, the t-test of two independent samples, and the N-Gain analysis. The results showed that there was a significant difference between the learning outcomes of reading skills of students in the experimental class and the control class. The sig value < 0.05, which shows a significant influence of the use of paragraph puzzle media on reading learning outcomes. N-Gain analysis showed that the improvement in learning outcomes in the experimental class was in the high category, while in the control class it was in the medium category. These findings show that paragraph puzzle media is effective in improving students' reading skills, especially in understanding the content of reading texts, arranging paragraphs logically, and increasing students' activeness and motivation to learn. Theoretically, this research enriches the discourse on Arabic language learning media by demonstrating that paragraph puzzle media plays a significant role in enhancing reading comprehension processes, particularly in integrating linguistic knowledge, text coherence, and higher-order thinking skills in reading skills. Future research is recommended to apply paragraph puzzle media in different educational contexts and with larger samples in order to obtain more comprehensive results.